INEAS’s Cost-Effectiveness Analysis of Vemurafenib: Paving the Way for Value-Based Pricing in Tunisia - Mouna Jameleddine; Nabil Harzallah; Hela Grati; Marie Christine Odabachian Jebali; Jaafar Chemli; Sebastián García Martí; Natalie Soto; Andrés Pichon-Riviere; Chokri Hamouda (Journal of Market Access & Health Policy)
The Tunisian Health Technology Assessment (HTA) body, INEAS, conducted a cost-effectiveness analysis (CEA) of vemurafenib in the treatment of locally advanced or metastatic BRAF V600-mutated melanoma. The objective of this analysis was to enable the use of value-based pricing as a new approach to price negotiation. This study was part of a broader HTA report that was prepared in response to a joint request from the regulatory authorities and the CNAM, Tunisia’s compulsory insurance scheme. Our analysis was based on a probabilistic Markov cohort model that calculated the costs and quality-adjusted life years (QALY) associated with vemurafenib compared to the standard of care from a public payer perspective. The CEA indicated that vemurafenib provides a gain of 0.38 life years (1.78 vs. 1.4) for an incremental cost of USD 101,106.62 from the perspective of the main public payer (CNAM). This study revealed an incremental cost-effectiveness ratio (ICER) of 163,311.40 USD/QALY and 163,911.46 USD/QALY, respectively, from the CNAM and public health facilities’ perspectives. Vemurafenib cannot be considered cost-effective in terms of what has normally been considered a reasonable willingness to pay (WTP) in Tunisia. A significant price reduction would be necessary to bring the incremental cost-effectiveness ratio to an acceptable level.